"You see, one day they cut": The evolution, expression, and consequences of resistance for women who oppose female genital cutting. Issue 7 (16th November 2016) - Kahn, Sarilee
ABSTRACT: It is estimated that more than 200 million women alive today have undergone female genital cutting (FGC). While emerging evidence shows that attitudes toward FGC may evolve for immigrants as they acculturate to the host country, scant empirical research explores how women come to oppose the practice. This qualitative study used grounded theory methods to explore the trajectory of resistance to FGC for seven women circumcised in childhood who sought asylum in the United States as adults to protect their daughters from the practice. Participants originated from Burkina Faso, Guinea, The Gambia, and Chad. Analysis revealed nine themes tracing the evolution of resistance to FGC and other gender role norms for participants: coercion, threat, and retribution narratives; traumatic memories of circumcision; growing awareness of the personal implications of circumcision; emergence of critical thinking; trangressive thoughts and acts; navigating the consequences of resistance; everyday reinforcement; negotiating resistance dilemmas; and making meaning of resistance. In contrast to previous studies linking opposition to FGC to post-settlement acculturation or pre-migration exposure to organized international human rights campaigns, findings of this study indicate that traumatic memories of the circumcision rite, combined with the capacity to reflect on "taken for granted" cultural practices and to employ critical thinking skills, may lead to resistance to FGC for some women. Furthermore, findings highlight that FGC, and opposition to it, has lasting consequences for women from societies where the practice is embraced, and these consequences persist after migration. Practice and policy recommendations are drawn from the analysis.